Chapter 3.1 From Conceptualisation to Action – The Quest for Understanding Attitudes of Research Managers and Administrators in the Wider World - Susi Poli; Cristina Oliveira; Virág Zsár (Emerald Publishing Limited, 2023)
This chapter examines various definitions and perceptions of Research Management and Administration (RMA) from individuals both from within and outside the profession to gain a wider understanding of this field. These definitions and perceptions are expected to trigger reflections on where the boundaries of the profession are more likely to be. To do so, the authors utilise a mixed method that begins with a discussion of different definitions of RMA. Next, we move from conceptualisation to action and engage the reader by presenting empirical insights from an analysis of specific training programmes within RMA, shedding light on the profession's distinctive features from an insider's perspective. Lastly, we delve into the case study of the project foRMAtion, a training program that introduces RMAs as the `Professionals at the Interface of Science.' This case study allows us to explore how individuals outside the RMA profession, such as teachers and students participating in its training courses, perceive and understand RMA.
10.1108/978-1-80382-701-820231019; 10.1108/978-1-80382-701-820231019; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262